Mexican Messiah : Andrés Manuel López Obrador - Grayson, George W., 1938-2015 (Book collections on Project MUSE., 2007)
"Grayson views Lopez Obrador as quite different from populists like Chavez, Morales, and Kirchner and argues that he is a "secular messiah, who lives humbly, honors prophets, gathers apostles, declares himself indestructible, relishes playing the role of victim, and preaches a doctrine of salvation by returning to the values of the 1917 Constitution - fairness for workers, Indians' rights, fervent nationalism, and anti-imperialism.""--Jacket.